1
$\begingroup$

Factoring:

$$f_{n+1}\geq r^{n-2}+r^{n-3}$$ Factoring out a common term of $r^{n-3}$ from line (2), we get: $$f_{n+1}\geq r^{n-3}(r+1)$$

I don't understand how to factor out r^(n-3) to get that result.

$\endgroup$
  • $\begingroup$ $r^{n-3} r^{1} = r^{n-3+1} = r^{n-2}$. $\endgroup$ – AnonSubmitter85 Feb 11 '14 at 23:32
  • $\begingroup$ What two variables? $\endgroup$ – Martín-Blas Pérez Pinilla Feb 11 '14 at 23:33
  • $\begingroup$ Which result? btw, r^(n-3) = (1 + (r-1))^(n-3), use extended binomial theorem here $\endgroup$ – abstractnature Feb 11 '14 at 23:33
  • $\begingroup$ @Martín-BlasPérezPinilla r and n $\endgroup$ – compguy24 Feb 11 '14 at 23:34
  • 1
    $\begingroup$ $r^{n-2}+r^{n-3}$ is a polynomial of degree $n-2$ in one variable. $\endgroup$ – Martín-Blas Pérez Pinilla Feb 11 '14 at 23:35
2
$\begingroup$

$r$ to any power is a common factor of both. I'm sure you are familiar with the following rule for exponents: $r^a \cdot r^b = r^{a+b}$. The other thing you need to know is that $r^0 = 1$. Using this, we can factor out $r^c$ from any expression of the form $r^x + r^y$:

$$ r^x + r^y = r^c ( r^{x-c} + r^{y-c}) $$

In this case, we have $x=n-2$, $y=n-3$, and $c=n-3$, which gives $r^{n-3}(r+r^0) = r^{n-3}(r+1)$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.